Helical side chain chemistry of a peptoid‐based SP‐C analogue: Balancing structural rigidity and biomimicry. Issue 6 (10th April 2019) - Brown, Nathan J.; Lin, Jennifer S.; Barron, Annelise E.
Abstract: Surfactant protein C (SP‐C) is an important constituent of lung surfactant (LS) and, along with SP‐B, is included in exogenous surfactant replacement therapies for treating respiratory distress syndrome (RDS). SP‐C's biophysical activity depends upon the presence of a rigid C‐terminal helix, of which the secondary structure is more crucial to functionality than precise side‐chain chemistry. SP‐C is highly sequence‐conserved, suggesting that the β‐branched, aliphatic side chains of the helix are also important. Nonnatural mimics of SP‐C were created using a poly‐ N ‐substituted glycine, or "peptoid, " backbone. The mimics included varying amounts of α‐chiral, aliphatic side chains and α‐chiral, aromatic side chains in the helical region, imparting either biomimicry or structural rigidity. Biophysical studies confirmed that the peptoids mimicked SP‐C's secondary structure and replicated many of its surface‐active characteristics. Surface activity was optimized by incorporating both structurally rigid and biomimetic side chain chemistries in the helical region indicating that both characteristics are important for activity. By balancing these features in one mimic, a novel analogue was created that emulates SP‐C's in vitro surface activity while overcoming many of the challenges related to natural SP‐C. Peptoid‐based analogues hold great potential for use in a synthetic, biomimetic LS formulation for treating RDS. Abstract :